Experimental studies of mass transfer in caryopsis at grain oscillating drying - S. A. Pavlov; I. A. Pekhal’Skiy; R. A. Marin (Сельскохозяйственные машины и технологии, 2016)
At a continual heatsupply at the beginning of drying process intensity of a mass transfer from a caryopsis surface exceeds intensity of moisture supply from its center to a surface. Thus the moisture content gradient in the caryopsis increases more than a difference between equilibrium moisture content and surface one. In the course of drying intensity of a mass tranfer decreases because of predrying of surface layers, the gradient of moisture content decreases, the front of evaporation continuously goes deep, respectively, intensity of process decreases. The variable heatsupply when seeds and grains drying allows to intensify process at full preservation of their quality indicators. The aythors proved parameters of oscillating drying and studied a mass transfer in a caryopsis for three drying modes: without lying, with lying after the heating period and lying after the cooling period. They compared efficiency of the oscillating drying modes to the drying mode at a continual heatsupply. The mass transfer was studied in the course of drying, humidity of a caryopsis and its cover and kernel was defined. Regularities of a mass transfer are revealed, the optimum modes of oscillating drying are offered: (the proportion of the periods «heating - cooling» is equal 10:10 minutes, an 15 minutes lying after the period «heating»). Physical and mathematical models are offered. The equation for calculation of lying duration is received. It is recommended to use the oscillating mode of drying with lying which duration should be sufficient for moisture redistribution in the caryopsis that keeps quality of seeds and grain. The lying extends process of drying (by 5 percent for an lying warmed up grain and by 10 percent for not warmed up one) in comparison with the same mode without lying, but allows to lower specific costs of warmth by 20-25 percent. At the oscillating mode lying duration is expedient when moisture removal increases in direct ratio to time.